(untitled) (Polish Yearbook of International Law, 2025)
Arbitration award enforcement proceedings are the crucial point of any dispute, as even the most groundbreaking award is pointless if it cannot be executed. The issue of the enforceability of awards is especially interesting in the region usually omitted from discussions on alternative dispute resolution: West Asia and North Africa. Usually portrayed as a monolith, the Arab states counter this assumption by taking on a highly nuanced and jurisdiction-specific approach to international arbi tration. This paper presents snippets of recognition and enforcement legislation and the case law from three states: Egypt, characterised by its active engagement in inter national arbitration; the Kingdom of Saudi Arabia, traditionally vested in the legal tradition of Islamic law; and Iraq, which only recently acceded to the international award implementation system. These examples are employed to determine whether there are any region-specific similarities in domestic courts’ reasoning on international arbitration. The legislation and cases analysed herein provide a unique outlook on these underrepresented jurisdictions, characterised by firm attachment to national law and legal tradition and subjected to global currents of economic liberalisation.